The Numerical Investigations of Non-Polynomial Spline for Solving Fractional Differential Equations (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
We present a crossing approach based on the new construction of non-polynomial spline function to investigate the numerical solution of the fractional differential equations. We find the accuracy of the spline method and to presenting the completion of non-polynomial spline two examples for problems are used. To clarify, we present the numerical computations that can be used to solve difficult problems while the results are found and got to be in good error estimation with comparing exact solutions.